(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Marketing is an intrinsic aspect of the company environment. Given the breadth and depth of marketing’s inherent complexity, the digital component has been elevated to centre stage. The terms ’digital marketing’ and ’internet marketing’ are used interchangeably and refer to the same thing. Many businesses, especially startups on the cusp of their big break, struggle to establish the optimal marketing strategy that will help them transition successfully from the laboratory to the consumer market. The B2B market is where the author’s own passion and lack of time for study have led her to concentrate.